Essentials of Travel Medicine for Practicing Physicians: A Review - Swayam Pragyan Parida; Alajangi Bhargavi; Arvind K. Singh; Abhisek Mishra; Chandrakant Lahariya (Preventive Medicine: Research & Reviews, 2025)
The increased international and global mobility heightens health risks, including region-specific infectious diseases and the possibility of global transmission of diseases. In this backdrop, the travel medicine has become an important field of work for preventing and managing travel-related health concerns. This article delves into what is travel medicine, its relevance, and how primary care physician can play a bigger role in travel medicine. More specifically, the travel clinics play a vital role by offering vaccinations, pre-travel consultations and disease surveillance. However, there are persisting challenges in travel medicines, such as a lack of comprehensive travel vaccine policies, limited public–private collaboration and inadequate digital health infrastructure. The article provides a global overview with India as an example for travel medicine. The authors concludes that there is an urgent need for structured travel health policies, improved training for primary care physicians and greater integration of travel medicine into public health systems to mitigate health risks and strengthen global health security.